2011
DOI: 10.1007/s00421-011-2213-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of road incline and body position on power–cadence relationship in endurance cycling

Abstract: In race cycling, the external power-cadence relationship at the performance level, that is sustainable for the given race distance, plays a key role. The two variables of interest from this relationship are the maximal external power output (P (max)) and the corresponding optimal cadence (C (opt)). Experimental studies and field observations of cyclists have revealed that when cycling uphill is compared to cycling on level ground, the freely chosen cadence is lower and a more upright body position seems to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…14 From a theoretical perspective, cyclists should choose a cadence near C opt to maximize P ext for the given task or to minimize peripheral fatigue at a given P ext . Results from previous studies showed that both FCC 3 and C opt 18 were significantly lower during uphill cycling than during cycling on level ground with the same body position. Taken together, these results suggest that both FCC and C opt are affected in a similar way by road incline, but no study has addressed whether the difference between FCC and C opt is the same independent of road incline.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…14 From a theoretical perspective, cyclists should choose a cadence near C opt to maximize P ext for the given task or to minimize peripheral fatigue at a given P ext . Results from previous studies showed that both FCC 3 and C opt 18 were significantly lower during uphill cycling than during cycling on level ground with the same body position. Taken together, these results suggest that both FCC and C opt are affected in a similar way by road incline, but no study has addressed whether the difference between FCC and C opt is the same independent of road incline.…”
mentioning
confidence: 82%
“…To improve the reliability of the measurements, the participants were asked to control a number of variables; for the details see Emanuele and Denoth. 14,18 The purpose of the first test session was to determine individual FCC and estimate the individual P ext at maximal lactate steady state (P MLSS ). The purpose of the second and third test sessions was to estimate C opt and P max at MLSS when cycling on level ground with DP and when cycling uphill with UP, respectively.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations